Communal Land Rights of Malay People in North Sumatera: Power, State and Deulayatisasi - Ikhsan, Edy (Indonesia Law Review, 2014)
This article aims to unravel a shift of control / ownership of communal land of the Malays of Deli in North Sumatra. The commonly well-known communal lands, before the arrival of the Dutch colonial, was still inherent with the authorities of villages and was evolutionarily taken over by the foreign planters through concessionary contracts, which were dully signed by the Sultanate of Deli and the said foreign planters. The Indonesian independence in 1945 and the period that went beyond had in fact not contributed any improvement of the situation and instead it had exacerbated social and legal relations between the Malays of Deli and their ancestral lands. The said successful state laws had been so successful to keep these local natives away from their most important resource of life, namely their very lands. “Deulayatisasi” through state laws that was heavily oriented to the interests of capitalization to have seemingly been so successful to curtail the long journey of communal land rights in this country that seemed to have been pioneered by Van Vollenhoven during the early period of 20th century. The customary land law, in Indonesia, will someday become a kind of a beautiful story in the course of historiographical laws of Indonesia.